Ethno-veterinary Use of Medicinal Plants in the Selected Districts of Siltie Zone, Southern Ethiopia - Gensa, Ufaysa; Dureti, Ensarmo, B.; Redwan, Anwar, C. (International Journal of Livestock Research, 2024)
Despite the wide use of traditional medicinal plants to treat animal and human ailments in Siltie Zone Ethiopia, the detailed ethno-veterinary knowledge was unexplored. To investigate the ethno-veterinary medicinal plants used in the selected districts of Siltie Zone, Southern Ethiopia. To identify and collect data related to medicinal plants and their traditional use, the pre-tested, semi-structured questionnaire-based survey was followed. The elderly willing farmers and experienced traditional healers were involved by using snowball sampling procedures from purposively selected study districts. Subsequently, the plant specimens were caught their leaves were collected, pressed and the identification of the plant was done within Werabe University in the Department of Biology. In the survey, 39 plant species and 35 genera from 26 families were identified and documented for treating 30 types of domestic animal diseases. The majority of plant species were grouped under the family Solanaceae (10.3%). The most frequently used plant part for remedy preparation was leaf 48 (58.3%), followed by root 16 (19.1%), seed 12 (14.3%) fruit 4 (4.7%), bark 2 (2.4%), and stem 1 (1.2%). It was found that most of the remedial preparation was delivered through the oral route (63.1%), followed by nasal (25%), topical (10.7%), and another route (1%). The highest fidelity (FL) value was recorded for Brassica carinata (A.) Br. (100%) and Schinus molle L. (100%), while the lowest was Phytolacca dodecandra L’Her (50%). The reproductive disease ailment category showed the highest (0.75) Informant Consensus Factor (ICF), while the ICF value of (0) was observed for external parasitic infestation and wound. In direct matrix ranking computed, Vernonia amygdalina Del. is the largest multipurpose use plant. Conclusion: The present study showed a rich knowledge of traditional medicinal plant use for animal disease treatment in the study districts and necessitated their conservation for future generations. The findings indicated a need for further investigation to determine the active medicinal agent, toxicity, and efficacy of medicinal plants that the traditional healers in the study districts used.